PENGARUH AKUNTANSI FORENSIK DAN SISTEM PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PADA ORGANISASI SEKTOR PUBLIK - Bambang Arianto; Gema Ika Sari (Accounting Journal of Ibrahimy (AJI), 2026)
This study aims to examine the effect of forensic accounting and internal control systems on fraud prevention in public sector organizations. Fraud in the public sector remains a critical issue because it is directly related to budget governance, public service accountability, bureaucratic integrity, and public trust in government institutions. This study employed a quantitative approach using a survey method involving 35 respondents who were associated with financial management, internal auditing, supervision, and administration in public sector organizations. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS application to examine the influence of the independent variables on fraud prevention in public sector organizations. The findings indicate that forensic accounting has an effect on fraud prevention, while forensic accounting also affects the internal control system. In addition, forensic accounting and internal control systems each have a positive effect on fraud prevention. This study further confirms that the better the implementation of forensic accounting and internal control systems, the greater the ability of public sector organizations to prevent potential fraud.